DEVELOPMENT OF CHEM QUARTET LEARNING MEDIA ON ACID AND BASE MATERIALS - Siti Fatonah; Cucu Zenab Subarkah; Sari Sari (Gunung Djati Conference Series, 2021)
This study aims to analyze the results of the product validation test for Chem Quartet learning media on acids and bases and to describe the appearance of the Chem Quartet learning media products on acids and bases. The method used in this research is DBR (Design Based Research). The research procedure consists of several stages including Analysis, Design, Development, Implementation, and Evaluation. This research uses qualitative and quantitative data types. The instruments used included validation test questionnaires for quantitative data and flowcharts and storyboards for qualitative data. The results of the validation test in this study obtained an average rcount in all aspects of 0.9791, thus it can be concluded that the Chem Quartet media was declared valid.